Avaliação de projetos na presença de volatilidade: estudo de caso de empresas no setor de telecomunicações - Yoshida, Sandra Kassumi (2008)
When companies decide whether they should invest or not in a long run (5 to 10 years ahead) investment project, some alternative methodologies to the Discount Cash Flow (DCF) may become useful in order to confirm the business feasibility or to define the best moment to start the enterprise. These analysis take into consideration both the cash flow uncertainty and the project starting date flexibility. It can also be built using a stochastic approach, such as the differential equation solutions for geometric Brownian motion. Under certain conditions, project opportunities can be seen as call options with no maturity date, as the model proposed by McDonald-Siegel (1986) for the decision makers process and the optimum moment to start the project. This work analyses the feasibility of investments in the telecommunication market using non deterministic models, where the most relevant variable is the return dispersion, i.e., the variance represents the risk associated to the enterprise.